2018
DOI: 10.18203/2349-2902.isj20182081
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the depth of tumor and neck node metastasis in early carcinoma of tongue

Abstract: INTRODUCTIONTongue squamous cell carcinoma (TSCC) is one of the commonest cancers within the oral cavity. Incidence of tongue cancer in India is second highest in the world. 1 TSCC is significantly more aggressive than other forms of oral cancer, with a high propensity of local invasion and spread, and a high recurrence rate.1,2 It has been reported that 40% of all TSCC patients have neck metastasis at the time of diagnosis.3 Patients with earlystage TSCC (T1/T2N0) showed occult nodal metastasis in approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In the present study, the number of males (84%) were more than females (16%). This is similar to the studies of Selvamani et al, Kshirsagar et al and Ahmad et al [4][5][6] Higher incidence of carcinoma in males can be attributed to the earlier starting of consumption of alcohol and tobacco in the male population compared to the female population.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the number of males (84%) were more than females (16%). This is similar to the studies of Selvamani et al, Kshirsagar et al and Ahmad et al [4][5][6] Higher incidence of carcinoma in males can be attributed to the earlier starting of consumption of alcohol and tobacco in the male population compared to the female population.…”
Section: Discussionsupporting
confidence: 91%
“…28 Our study also shows that male predominance in tongue squamous cell carcinoma with male: female ratio of 3:1 similar to study conducted by Hakeem et al 29 In our study, level IIA lymph node is the most common site for occult nodal metastasis followed by level IB and level IV which is similar to study conducted by Pet al who also concluded that level II is most common neck node in tongue squamous cell carcinoma. 30 Jones et al in their study concluded that there is a strong correlation between thickness of tumor and risk of nodal metastasis. 8 O'Brient et al proposed that depth of tumor invasion is the most important measurable prognostic factor in early stage oral cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, we found an association between depth of invasion (DOI) and neck node metastasis in cases of carcinoma tongue and carcinoma buccal mucosa. 2,[4][5][6]8,[10][11][12] Eight mm in oral cavity carcinoma seems to be the cut off depth of invasion above which incidence of nodal metastasis increases. 10 Cervical metastatic rates (pN+) are significant at depth more than eight mm in oral tongue and buccal mucosa carcinoma in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancers are the most common cancers in the developing countries especially in Southeast Asia. 1,2 Oral cancer is the most common cancer in India, as four out of ten of all cancers are oral cavity cancers. 3,4 Cervical lymph node metastasis has remained the most important prognostic factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation